Pendekatan Arsitektur Modern Kontemporer pada Pengembangan Bandar Udara Dewadaru Karimunjawa di Kabupaten Jepara (Selasar, 2022)
The development of Dewadaru Karimunjawa airport in Jepara Regency is carried out to accommodate all movements of air transportation modes in the next 20 years. This is in response to the increasing number of tourists heading to Karimunjawa Island, where Karimunjawa Island is an archipelago tourist attraction that is included in the Karimunjawa National Park area. The development in question is to respond to the condition of Dewadaru Airport based on spatial capacity and tamping capacity, which is still far from the feasibility of the role, function of use, hierarchy and classification of the airport nor does it display regional characteristics / identity as well as green airport.